Integration of Digital Platforms and Legacy Media in The Promotion of Emerging Artists - Dudiak, Tetiana (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
This article examines how emerging artists gain visibility when digital platforms (short-form video, audio streaming, and video hosting) are coordinated with legacy media exposure (broadcast, press, and event coverage). Relevance is determined by fragmented audience attention, algorithmic discovery, and the signaling capacity of curated media gatekeepers. Novelty is provided through an integrated pathway model that links platform affordances (save-to-app flows, playlist placement, user-generated circulation) with legacy-media credibility cues and event-based attention spikes. The article aims to systematize cross-channel promotion strategies for early-career artists and their representatives. The analytical approach relies on comparative synthesis of recent peer-reviewed research on short-form video labor, playlist intermediation, streaming conversion, and music video persuasion, complemented by sector analytics on recorded-music ecosystems. The findings specify the conditions under which platform exposure leads to sustained discovery and identify governance risks (opacity, volatility, dependence) that shape predictable career progression. The article is helpful for talent agencies, producers, and cultural organizations designing promotion roadmaps.